2018
DOI: 10.1002/jsfa.9185
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of alfalfa yield and quality by plant growth‐promoting rhizobacteria under saline‐alkali conditions

Abstract: Two PGPR strains were isolated from the rhizosphere of alfalfa in saline-alkali conditions. Both strains could promote alfalfa growth in saline-alkali soil, and could be used as biofertilizer to promote plant growth under stress and reduce environmental pollution caused by fertilizers simultaneously. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…Moreover, no difference between the inoculated plants with both bacteria showed that either bacterium could increase dry weight, height, and leaf number under salinity. The reports showed in inoculated plants with bacteria, root length and nutrient absorption such as phosphor, potassium, and nitrogen (Babalola 2010), synthesis of auxins, cytokinins, and gibberellins (Glick et al 2007), growth rate, and dry mass production were higher than noninoculated plant under stress and control conditions (Gupta et al 2015;Xiao et al 2018;Liu et al 2019;Trdan et al 2019). Liu et al (2019) and Xiao et al (2018) suggested that inoculation with rhizomicrobiome increased significantly plant growth in alfalfa plants and also plant biomass was affected by the composition of the rhizomicrobiome, soil pH, N, P, and plant growth stage and species.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no difference between the inoculated plants with both bacteria showed that either bacterium could increase dry weight, height, and leaf number under salinity. The reports showed in inoculated plants with bacteria, root length and nutrient absorption such as phosphor, potassium, and nitrogen (Babalola 2010), synthesis of auxins, cytokinins, and gibberellins (Glick et al 2007), growth rate, and dry mass production were higher than noninoculated plant under stress and control conditions (Gupta et al 2015;Xiao et al 2018;Liu et al 2019;Trdan et al 2019). Liu et al (2019) and Xiao et al (2018) suggested that inoculation with rhizomicrobiome increased significantly plant growth in alfalfa plants and also plant biomass was affected by the composition of the rhizomicrobiome, soil pH, N, P, and plant growth stage and species.…”
Section: Discussionmentioning
confidence: 99%
“…The visual appearance of leaves also revealed that Cd affected the overall morphology, whereas bacterial treatment could help the plant to produce healthier leaves. Recently, Enterobacter aerogenes was also reported to possess different PGP properties and to significantly enhance the overall growth, yield and quality of alfalfa, even under stress conditions …”
Section: Discussionmentioning
confidence: 99%
“…So NaHCO 3 stress has become one of the major constraints to crop yield and agricultural sustainability [13]. Under the stress of NaHCO 3 , inoculation of Enterobacter aerogenes LJL-5 and Pseudomonas aeruginosa LJL-13 increases alfalfa yield and quality [14]. Application of Trichoderma asperellum decreases the infection incidence of pathogenic fungi and alleviates NaHCO 3 stress in poplar [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, 669 enriched and 1296 depleted species were identified. The top 10 NaHCO 3 -responsive genera with highest number of species were Streptomyces (81), Pseudomonas (70), Bacillus(22), Rhizobium(22), Rhodococcus(19), Bradyrhizobium(17), Mycobacterium(17), Micromonospora(15), Pseudoalteromonas(14), and Sphingomonas(14). Based on the 16S rRNA amplicon sequencing, the genera Pseudomonas, Rhizobium, Bradyrhizobium, Mycobacterium, and Sphingomonas were still in response to NaHCO 3 tress (Additional file 4:Table S5).…”
mentioning
confidence: 99%